Organoid Models for Salivary Gland Biology and Regenerative Medicine - Chen Zhao; Cuida Meng; Na Cui; Jichao Sha; Liwei Sun; Dongdong Zhu (Stem Cells International)
The salivary gland is composed of an elegant epithelial network that secrets saliva and maintains oral homeostasis. While cell lines and animal models furthered our understanding of salivary gland biology, they cannot replicate key aspects of the human salivary gland tissue, particularly the complex architecture and microenvironmental features that dictate salivary gland function. Organoid cultures provide an alternative system to recapitulate salivary gland tissue in vitro, and salivary gland organoids have been generated from pluripotent stem cells and adult stem/progenitor cells. In this review, we describe salivary gland organoids, the advances and limitations, and the promising potential for regenerative medicine.